Quantificação de enterococcus faecalis por métodos de cultivo após o uso de antimicrobianos intracanais na terapia endodôntica - Có, Flavia de Fátima Zanon Oliveira (2012)
This in vitro study evaluated the susceptibility of Enterococcus faecalis (E. faecalis) to different intracanal antimicrobials used in endodontic therapy. Thirtysix human molars previously extracted were autoclaved and inoculated with E. faecalis (ATCC 29212) for 14 days. After the contamination period the specimens were instrumented by rotatory files and subdivided into two experimental groups (n = 26) and one control group (n = 8). All procedures were performed in laminar flow hood. The experimental group was irrigated with 5,25% NaOCl and divided according to intracanal medication: group 1 (n = 13): 2% chlorhexidine gel and group 2 (n = 13): Ca(OH)2. The control group was treated with 0,85% saline. Four samples were processed for each specimen: after the infection period (A), immediately after instrumentation (B), 14 days after healing medication (C) and seven days after removing the intracanal medication(D). Two specimens were infected and evaluated by SEM to observe the contamination of the dentinal tubules by this microorganism. There was a significant reduction in the Colony Forming Units (CFU) after using 5,25% NaOCl as an endodontic irrigant and after usingthe intracanal medications based on Ca(OH)2 and 2% chlorhexidinegel. Better results were obtained with 2% chlorhexidine gel, although there were not statisticals differences between these two substances. After seventh day without intracanal medication there was significant increase in the number of CFUs for group1 and 2. This methodology was capable to achieving the observation by SEM of the contamination in the main canal and dentinal tubules by E. faecalis. The 5,25% NaOCl was an effective irrigant. The two intracanal medications were capable to reduce the number of the E. faecalis in the root canal system after 14 days, but no antimicrobial was effective in preventing recontamination of the main canal and dentinal tubules by this microorganism, after seven days without intracanal medication.